2007
DOI: 10.1117/12.732283
|View full text |Cite
|
Sign up to set email alerts
|

ATCG nucleotide fluctuation of Deinococcus radiodurans radiation genes

Abstract: The radiation resistance-repair genes in Deinococcus radiodurans (DR) and E-coli were analyzed in terms of the A, T, C, G nucleotide fluctuations. The studied genes were Rec-A, Rec-Q, and the unique DR PprA gene. In an ATCG sequence, each base was assigned a number equal to its atomic number. The resulting numerical sequence was the basis of the statistical analysis. Fractal analysis using the Higuchi method gave a fractal dimension increase of the Deinococcus radiodurans genes as compared to E-coli, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 0 publications
0
38
0
1
Order By: Relevance
“…Sixteen 1-sequence numerical representations have been presented and compared to classify untrained exon and intron sequences in the spectral domain, in which the K-Quaternary Code I yields attractive performance. When comparing each of the sixteen windowed 1-sequence numerical representations using WL = [9,15,24] bases to a non-windowed 4-sequence numerical representation (such as the Voss representation), the speed improvement ratio increases as SL increases which favours long nucleotide sequence analysis. The results obtained indicate the methodologies introduced in this article for exon and intron sequence classification are applicable to the genomes of the human and other model organisms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen 1-sequence numerical representations have been presented and compared to classify untrained exon and intron sequences in the spectral domain, in which the K-Quaternary Code I yields attractive performance. When comparing each of the sixteen windowed 1-sequence numerical representations using WL = [9,15,24] bases to a non-windowed 4-sequence numerical representation (such as the Voss representation), the speed improvement ratio increases as SL increases which favours long nucleotide sequence analysis. The results obtained indicate the methodologies introduced in this article for exon and intron sequence classification are applicable to the genomes of the human and other model organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of 4L × log 2 (L) over NW × N × log 2 (N) gives a speed improvement ratio. A plot of the speed improvement ratio against SL for WL = [9,15,24] bases is shown in Figure 10. As seen from Figure 10, it can be observed that a windowed 1-sequence representation with WL = [9,15,24] bases offers a possible speed advantage over a non-windowed 4-sequence representation and the speed improvements increases as SL increases.…”
Section: Speed Performancementioning
confidence: 99%
See 3 more Smart Citations